Theoretical basis of soil hydrology in the works A.A. Rode and modern approaches to the description of water movement and equilibrium in the soil - E. V. Shein (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
Classical Russian soil hydrology created by works of A.A. Rode, his colleagues and associates is based on the concept of water forms in the soil and soil hydrological constants. At the present state of development the soil hydrology uses all conceptual approaches designed by A.A. Rode and his colleagues which allow us to characterize the soil hydrology as an actively developing science, which has its own historical path, principles, application limits, benefits and possible long-term development path, which uses the developed and experimentally confirmed by A.A. Rode concept of “capillary-suspended” and “capillary-backed” water and, accordingly, the field and the capillary soil water capacities. The current stage of soil hydrology is characterized by the active application of quantitative approaches. At the present, in hydrology the soil water retention curve takes the central place, which stand out as the break point corresponding to the capillary water capacity and values of “air entrance pressure”. The examples describe the nonlinear characteristics the water retention curves with clearly dedicated air inlet pressure for heavy soddy-podzolic soil, gray forest soil and chernozem. Shaped hydrological characteristics of A. A. Rode such as “capillary-suspended” and “capillary-backed” soil water are still actively used in actual educational process.